2020
DOI: 10.11604/pamj.2020.37.363.26211
|View full text |Cite
|
Sign up to set email alerts
|

Profil épidémiologique et clinique des enfants atteints de la maladie à Corona Virus (COVID-19) au Centre de Traitement des Epidémies et Prévention des Infections (CTEPI) du CHU de Donka à Conakry

Abstract: La COVID-19 est due au virus SARS-CoV-2 génétiquement semblable au virus du syndrome respiratoire aigu sévère (SARS). En pédiatrie, les formes cliniques ont un caractère bénin. En Guinée, suite à la pandémie du COVID-19 dont l´épicentre était Conakry, des cas pédiatriques ont été observés au CTEPI de Donka. L´objectif de cette étude était de déterminer leur profil épidémiologique. Etude transversale de type descriptif de 04 mois chez les enfants de 0 à 16 ans admis au CTEPI Donka. Sur 7308 patients provenant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
2
3
1
1
Order By: Relevance
“…With an age range of 0 -19 years, it had a mean age of 10.89 ± 7 years. This result was different from that of Camara et al [4] who evaluated the epidemiological and clinical profile of children with COVID in a town in Guinea. It had a more predominant age range of 0 -4 years and an average age of 7 years.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…With an age range of 0 -19 years, it had a mean age of 10.89 ± 7 years. This result was different from that of Camara et al [4] who evaluated the epidemiological and clinical profile of children with COVID in a town in Guinea. It had a more predominant age range of 0 -4 years and an average age of 7 years.…”
Section: Discussioncontrasting
confidence: 97%
“…The sex ratio was 0.83. This is similar to the study by Camara et al [4] who found a female predominance of 60.32%, this predominance in Camara was due to the demography of Guinea, which is predominantly female. But a study by Meguieze et al in the vicinity of Yaoundé [2] showed a male predominance of 52%.…”
Section: Discussionsupporting
confidence: 92%
“…En Guínea, Camara et al, 15 al analizar a niños menores de 17 años, entre los que predominaron las muje- En la curva de casos confirmados por día de inicio de síntomas se distingue claramente el incremento del número de casos entre noviembre de 2020 y febrero de 2021, hecho que no se visualiza entre marzo y noviembre, donde la curva se mantuvo con nuevos casos confirmados no tan elevados (Figura 1).…”
Section: Discussionunclassified
“…Approximately 4 million children in the United States were reported to have been infected with coronavirus disease 2019 (COVID‐19) as of May 2021 1–3 . Although most children had mild or asymptomatic disease, several thousands required hospitalization, and hundreds have died due to the disease and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 4 million children in the United States were reported to have been infected with coronavirus disease 2019 (COVID-19) as of May 2021. [1][2][3] Although most children had mild or asymptomatic disease, several thousands required hospitalization, and hundreds have died due to the disease and its complications. Children with compromised disease states are more likely to experience severe effects of COVID-19; however, even healthy children develop severe disease, according to the Centers for Disease Control and Prevention.…”
Section: Introductionmentioning
confidence: 99%